Mapping of records-keeping practices of selected private educational institutions in Metro Manila towards the creation of a classification and filing guide for Saint Poveda College - Asuncion, Emelita B.; Olgado, Benedict S.; Lagrama, Eimee Rhea, C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study focused on the prevailing records-keeping practices of selected private educational institutions in Metro Manila to be able to come up with an effective classification and filing guide for Saint Pedro Poveda College (SPPC) based on the concept of International Standard on Archival Description better known as ISAD(G). St. Scholastica's College Manila, St. Paul University and St. Mary's College in Quezon City and Saint Pedro Poveda College are the schools surveyed for this study.
The archivists/records managers of the respective colleges that were surveyed, along with the 22 records coordinator of SPPC provided the complete files/records list where the classification and filing guide for SPPC were drawn. The study used the descriptive survey method of research as instrument to gather the data. An ocular inspection and interviews were also conducted to further extract necessary data for analysis.
The survey revealed that personnel in-charge of records-keeping are not properly trained resulting to varied system in classification and filing. There are no existing manual on filing and classification. Upon approval, all four colleges permit access and loan of records with students and administrators as the most common borrowers of materials. The most common problem on storage is the lack of space that can accommodate the growing number of collection highlighted by the lack of electronic data-base for fast and easy retrieval. Inventory of records is conducted only to determine the existing files of each office with no existing disposition schedule. All respondents do not have disaster preparedness program that is necessary for business continuity in case of calamities. The only measure employed is preventive in nature which only controls the physical maintenance of the record.
The most common storage is folders fastened together by fastener, rubber bands and paper clips and kept in file boxes. The institution's museum serves as source of promotion of the archives including exhibits and brochures. Files are commonly filed in alphabetic-numeric and chronological order and are identified by color coded labels using index cards as the most common finding aids. Lastly, the concept of records continuum is not practiced and not popular among the surveyed schools.
The following recommendations are proposed: a) staff training for records personnel; b) creation of policies and procedures; c) constitution of a committee for advisory and system improvement; d) inclusion of digitally-born records in the collection; e) provision for adequate storage space; f) taking advantage of technology and use it for easy access and fast retrieval of data; g) proper disposal of records; h) to use the Web as promotional tool to advertise the archives; i) collaboration among offices to develop an effective classification and filing system; j) integration of records management and archives using the records continuum model; k) seeking the support of the management to be able to establish a successful Records Management Program.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Records -- Management; Private schools -- Philippines -- Manila Metropolitan Area